Thermodynamic Models and Central Composite Design for Calcium Sulfate Dihydrate Solubility - KIRAN YILDIRIM, BERÇEM; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2020)
The solubility of calcium sulfate dihydrate (gypsum) was measured in HCl solutions in the presence of Cr3+ and Fe3+ ions at various temperatures. The results indicate that the solubility of gypsum is fairly dependent on the concentrations of HCl and impurities, i.e., Cr3+ and Fe3+ ions. The experimental data were analyzed by applying the Buchowski-Kiazczak (lambda h) model and the modified Apelblat model. Some thermodynamic parameters, such as the standard molar dissolution enthalpy, the standard molar Gibbs energy, and the entropy of solutions, were calculated by Van't Hoff analysis and Gibbs equation. The influences of the concentrations of both HCl and impurities, i.e., Cr3+ and Fe3+ ions, and temperature on the gypsum solubility were examined by applying the central composite design.
Keywords: Calcium sulfate dihydrate; Central composite design; Metal ions; Solubility; Thermodynamic models; ENTHALPY-ENTROPY COMPENSATION; ACID; WATER; CRYSTALLIZATION; MIXTURES; SYSTEMS; DRUGS